Solving consumption models with multiplicative habits - Christopher D. Carroll (The Johns Hopkins University, Department of Economics, 2000)
This paper provides derivations necessary for solving an optimal consumption problem with multiplicative habits and a CRRA 'outer' utility function either for a microeconomic problem with both labor income risk and rate-of-return risk or for a macroeoconomic representative agent model.
Keywords: D91; E21; O40; 330; formation; relative consumption; economic growth; representative agent; Mikroökonomische Konsumfunktion; Verhaltensökonomik; Prinzipal-Agent-Theorie; Wirtschaftswachstum; Theorie